Possibilities for evaluation to foster the soft skills of critical thinking, creativity, and communication in higher education - Dadelo, Stanislav (Creativity Studies, 2025)
Soft skills are the foundation of a solid and consistent lifelong education in a changing world. Students’ self-reported achievement motivation is a good indicator of their level of self-awareness. A rigorous assessment of the process’ results is necessary for an effective soft skill education program. There are significant flaws in the way the university’s curriculum handles soft skill assessments. Therefore, the question is: given the resources at hand, how can one properly ascertain which soft skills requirements change the most over a university education? To identify changes at the start and finish of studies and prepare instruction for soft skill suggestions during university studies, this study intends to measure the differences in self-assessment indicators of students’ creativity, critical thinking, and communicative abilities in university settings. The purpose of this study is to verify a variety of tools for assessing students’ soft skills and figure out how effectively they can recognize variations throughout multiple university study stages. This could aid in the preparation of recommendations for soft skill instruction in courses, which could be beneficial for university graduates’ future employment. Among first- and last-year university students, a self-assessment study on soft skills was conducted. The results show that students’ soft skills are not equally impacted by their university education. The critical thinking abilities of first- and fourth-year students only tend to improve but do not differ reliably.